Impact of Epidemiological Publications among Health Professionals in Disease Surveillance – Experience from Jaffna, Sri Lanka - Chandrasekar, K.; Mahesan, S.; Bath, P.A. (International Journal of Multidisciplinary Studies (IJMS), 2017)
Epidemiological publications are generally published at national level as a source of feedback for surveillance data provided by the preventive health sector at regional and local levels. In this connection, WER and QEB published by the Epidemiology unit are considered as the chief source of current epidemiological information in Sri Lanka. This study explores the significance of these epidemiological publications, examines the awareness and utilisation of these publications among health staff, analyses the perception of health staff regarding the quality of information carried in these publications and assesses the influence of these publications on policy decisions. This study was carried out among health staff engaged in notifiable disease surveillance activities in Jaffna District, Sri Lanka. A qualitative approach, using in-depth semi-structured interviews was used. Even though WER and QEB are published to serve the purpose of disseminating epidemiological information related to Sri Lanka, their outreach is not satisfactory. In Jaffna, the factors such as limited circulation, lack of awareness, problems in accessibility, time delay in publication and language barrier are contributing to the poor utilisation of these publications among health professionals and health workers. Efforts should be taken at national level to ensure the accessibility and to improve the utilisation of these epidemiological publications. Initiatives at regional level to collect, collate and publish epidemiological information is also essential.
Keywords: Epidemiological publications; Health information access